Tailored Education Increased Capability and Motivation for Fall Prevention in Older People After Hospitalization - Naseri, Chiara; McPhail, Steven M.; Morris, Meg E.; Haines, Terry P.; Etherton-Beer, Christopher; Shorr, Ronald; Flicker, Leon; Bulsara, Max; Lee, Den-Ching A.; Francis-Coad, Jacqueline; Waldron, Nicholas; Hill, Anne-Marie (Frontiers in Public Health, 2021)
Recently hospitalized older people are at risk of falls and face barriers to undertaking fall prevention strategies after they return home from hospital. The authors examined the effects of tailored education delivered by physiotherapists on the knowledge (capability) and the motivation of older people to engage in fall prevention after hospital discharge. Utilizing data gathered from a recent trial, data was analyzed from 390 people who were 60 years and over without impaired cognition (>7/10 abbreviated mental test score) and discharged from three Australian hospitals. Motivation and capability were measured at baseline in the hospital and at 6-months after hospital discharge by blinded assistants using structured surveys. Bivariate analysis using generalized linear modeling explored the impact of education on the capability and motivation. Engagement in fall prevention strategies was entered as an independent variable during analysis to determine associations with capability and motivation. The education significantly improved capability [−0.4, 95% CI (−0.7, −0.2), p < 0.01] and motivation [−0.8, 95% CI (−1.1, −0.5), p < 0.01] compared with social-control at the time of hospital discharge. In contrast, social-control participants gained capability and motivation over the 6-months, and no significant differences were found between groups in capability [0.001, 95% CI (−0.2, 0.2), p = 0.9] and motivation [−0.01, 95% CI (−0.3, 0.3), p = 0.9] at follow-up. Tailored fall prevention education is recommended around hospital discharge. Participants still needed to overcome barriers to falls prevention engagement post hospitalization. Thus, tailored education along with direct clinical services such as physiotherapy and social supports is warranted for older people to avoid falls and regain function following hospitalization.